Boys who are born preterm show a relative lack of fat‐free mass at 5 years of age compared to their peers. (2nd December 2014) - Giannì, M. L.; Roggero, P.; Piemontese, P.; Morlacchi, L.; Bracco, B.; Taroni, F.; Garavaglia, E.; Mosca, F.
Abstract Aim Prematurity is associated with features of metabolic syndrome in young adulthood. We investigated the body composition and blood pressure of children born preterm. Methods A longitudinal, observational study was conducted with preterm infants who had a birth weight of <1500 g and a gestational age of <32 weeks. Growth and body composition were assessed by air displacement plethysmography at term equivalent age and at school age and were compared to those of 61 healthy, term breastfed subjects. Results A total of 63 preterm infants were enrolled. At term equivalent age, growth and fat‐free mass were lower in preterm infants than in term newborns, but fat mass was higher. At 5 years of age, children born preterm were still lighter and shorter than children born at term. When the results were analysed by gender, the fat‐free mass index was lower in boys born preterm than in their peers (12.1 ± 1.1 versus 13.0 ± 1.0 kg/h2 p < 0.005), whereas no difference was detected among girls. Diastolic blood pressure was higher in children born preterm than in children born at term (61.14 ± 7.8 vs 56.69 ± 8.2 mmHg, p = 0.009). Conclusion Boys born preterm showed a relative lack of fat‐free mass at school age compared to their peers.